Understanding Pet Humanization within International Business Markets: An Analytical Study of Human Psychology, Opportunities, and Impact in a Cross-Cultural Context - Tamilia, Lisa (Digital Repository of Theses - SSBM Geneva, 2024)
This research will examine the impact that pet humanization culture has on international pet markets. A focus on how businesses can capitalize on the positive impact pet humanization can make throughout the international landscape will be highlighted. Key data collection methods for this research will include but are not limited to, existing research and a proprietary survey developed by the researcher. The information gathered for this research study provides quantitative data relevant to pet humanization culture and its impact on global pet markets. Recommendations for future research and limitations of this research study are also included. The pet humanization survey created for this research study explored consistencies with literature review. The analysis included the topic of how pet owners view their pets in relationships and as part of their family. The pet humanization survey for this research study was consistent with findings from HABRI’s (2022) survey and statistics from Forbes Advisor’s Pet Ownership Statistics and Facts in 2023 (Megna, 2023) relating to pets as family and relationships. One research survey question for this academic thesis asked, “Do you consider your pet a part of the family &/or a “best friend”? 91.89% of those surveyed answered “yes” to this question. This is consistent with HABRI’s (2022) survey that showed 95% of those surveyed consider their pets as part of the family and 90% that considered having a close relationship with their pet. This is also consistent with Forbes Advisor’s Pet Ownership Statistics and Facts in 2023 (Megna, 2023) that showed 85% of dog owners and 76% of cat owners consider their pets to be a part of their family (Megna, 2023)